Increased Expression of Long Noncoding RNA LOC100506314 in T cells from Patients with Nonsegmental Vitiligo and Its Contribution to Vitiligo Pathogenesis - Ning-Sheng Lai; Hui-Chun Yu; Hsien-Bin Huang; Hsien-Yu Huang Tseng; Ming-Chi Lu (Hindawi Limited, 2023)
This study aimed to identify the abnormal expression of long noncoding RNAs (lncRNAs) in T cells from patients with vitiligo and to investigate their functional roles in the immune system. Using microarray analysis, the expression levels of RNA transcripts in T cells from patients with vitiligo and controls were compared. We identified several genes and validated their expression levels in T cells from 41 vitiligo patients and 41 controls. The biological functions of the lncRNAs were studied in a transfection study using an RNA pull-down assay, followed by proteomic analysis and western blotting. The expression levels of 134 genes were significantly increased, and those of 142 genes were significantly decreased in T cells from vitiligo patients. After validation, six genes had increased expression, and three genes had decreased expression in T cells from patients with vitiligo. T-cell expression of LOC100506314 was increased in vitiligo, especially CD4+, but not CD8+ T cells. The expression levels of LOC100506314 in CD4+ T cells was positively and significantly associated with the severity of vitiligo. LOC100506314 was bound to the signal transducer and activator of transcription 3 (STAT3) and macrophage migration inhibitory factor (MIF). Enhanced expression of LOC100506314 inhibited the phosphorylation of STAT3, protein kinase B (AKT), and extracellular signal-regulated protein kinases (ERK), as well as the levels of nuclear protein of p65 and the expression of IL-6 and IL-17 in Jurkat cells and T cells from patients with vitiligo. In conclusion, this study showed that the expression of LOC100506314 was elevated in CD4+ T cells from patients with vitiligo and associated the severity of vitiligo. LOC100506314 interacted with STAT3 and MIF and inhibited IL-6 and IL-17 expression by suppressing the STAT3, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), AKT, and ERK pathways. Enhanced expression of LOC100506314 in T cells may be a potential treatment strategy for vitiligo.